Using the pavesled to develop the skating musculature - Pollitt, D. J. (Strength and Conditioning Journal, 2004)
This article explores a new dryland training device to help train the skating-specific musculature in ice hockey. Coaches who wish to add more sport-specific training with a cost-effective product may find this article useful.